Lip Melanosis Postdermal Filler Injection: Second Case Report and Literature Review - Abdulrahman Abdullah Altariqi; Azizah Fahad Bin Mubayrik (Case Reports in Dentistry)
Oral pigmentation can arise from various factors, including physiological and pathological, or as a manifestation of an underlying systemic disease. We present an atypical case of dermal filler–related complication, in which clinical lip pigmentation was observed. This condition can pose a diagnostic challenge in accurately identifying its cause.